• Предмет: Алгебра
  • Автор: ieremia333
  • Вопрос задан 7 лет назад

Упростить выражения 2√5-√45+√3= 2√2-√18+√3= √5+√10-√20= √8-3√2+√6= 2√2*5√3*√6= 3√2*√5*4√10= √8*√6*√3-7= √8*√6/ √24 √5*√12/ √20 √15/√6*√10 √14/√6*√21 √3*√8/√6 √50*√6/ √12

Ответы

Ответ дал: fuit4zshit
0
2√5-√45+√3= 2√5-3√5+√3=√3-√5 2√2-√18+√3=2√2-3√2+√3=√3-√2 √5+√10-√20= √5+√10-2√5=√10-√5 √8-3√2+√6=2√2-3√2+√6=√6-√2 2√2*5√3*√6= 2√2*5√3*√6= 10√(2*3)*√6=10*6=60 3√2*√5*4√10=12√(5*2)*√10=12*10=120 √8*√6*√3-7=√(8*6*3)-7=4*3-7=12-7=5 √8*√6/ √24=√48 √24= √21= √2 √5*√12/ √20= √60 √20= √3
Похожие вопросы
4 года назад